Aspen plus® simulation studies of steam gasification in fluidized bed reactor for hydrogen production using palm kernel shell - Hussain, M. (Springer Verlag, 2017)
In this paper, a steady state simulation for hydrogen production from steam gasification of Palm kernel shell was developed and studied. The gasification pilot plant process has been modelled in Aspen Plus® using Gibbs reactor (R-Gibbs). The effects of different operating parameters using sensitivity analysis, including gasification temperature 600–900 °C and steam flow rate (1 to 2 kg/hr.), on hydrogen yields and Syngas composition were investigated. The simulation results have shown the main gas components in Synthesis gas were H2, CO, CO2, CH4. The product gas hydrogen yield increases with the increase in temperature. The hydrogen concentration improved from 22.52 vol. to 36.06 vol., but the CO concentration decreased from 37.53 vol. to 28.37 with increasing temperature from 650–900 °C under the operating parameters of the steam flow rate of 1.56 kg/hr. © Springer Nature Singapore Pte Ltd. 2017.